Cytosporone derivatives from the endophytic fungus Phomopsis sp. PSU-H188. (December 2017) - Kongprapan, Thippaya; Xu, Xin; Rukachaisirikul, Vatcharin; Phongpaichit, Souwalak; Sakayaroj, Jariya; Chen, Jing; Shen, Xu
Graphical abstract: Highlights: Two cytosporones (1 and 2) and 19 known compounds were isolated from Phomopsis sp. Known mycoepoxydiene showed potent cytotoxicity towards MCF-7 cells with an IC50 value of 9.27  μ M. Mycoepoxydiene displayed interesting glucose output inhibition with an IC50 value of 16.06  μ M. Known cytosporone B displayed protective activity against pancreatic β -cells with an EC50 value of 11.08  μ M. The glucose output inhibition of mycoepoxydiene and protective action of cytosporone B are reported for the first time. Abstract: Two new cytosporone derivatives (1 and2 ) were isolated from the endophytic fungus Phomopsis sp. PSU-H188 together with 19 known compounds. Their structures were elucidated by analysis of spectroscopic data. Known mycoepoxydiene showed potent cytotoxic activity towards both MCF-7 and noncancerous Vero cell lines with the respective IC50 values of 9.27 and 4.06 μM. It exhibited inhibition on glucose output in mouse primary hepatocytes with the IC50 value of 16.06 μM, but did not show cytotoxicity on primary mouse hepatocytes. Additionally, known cytosporone B displayed protective activity against INS-1 832/13 pancreatic β -cells by an EC50 value of 11.08 μM whereas known diaporthalasin displayed antibacterial activity against methicillin-resistant Staphylococcus aureus with an MIC value of 4 μg/mL. Both of them were noncytotoxic to Vero cells.